2002
DOI: 10.1590/s0085-56262002000400014
|View full text |Cite
|
Sign up to set email alerts
|

Heterozigosidade e assimetria do número de hâmulos em operárias adultas de Apis mellifera (Hymenoptera, Apidae)

Abstract: ABSTRACT. Heterozygosity and hammuli number asymmetry in adult workers of Apis mellifera (Hymenoptera, Apidae). Relationship between individual heterozygosity at particular loci (Mdh-1, Hk-1 ou Pgm-1) or average heterozygosity of the colony and asymmetry of the hammuli number of right and left wings was verified on adult workers of five Africanized and five European colonies of Apis mellifera. Our results demonstrated the importance of statistical tests to verify the type of asymmetry of the character studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
1
0
5
Order By: Relevance
“…In the analyses performed for this study, we observed that the shape represents better symmetry differences when compared to size, which are similar to results found by Del Lama, Gruber and Godóy (2002). Those authors also found that the shape of the wing contain better structures to asymmetry study, because it apparently is more affected by the environment when compared with the size.…”
Section: Discussionsupporting
confidence: 90%
“…In the analyses performed for this study, we observed that the shape represents better symmetry differences when compared to size, which are similar to results found by Del Lama, Gruber and Godóy (2002). Those authors also found that the shape of the wing contain better structures to asymmetry study, because it apparently is more affected by the environment when compared with the size.…”
Section: Discussionsupporting
confidence: 90%
“…Así mismo, estas variables en conjunto mostraron correlaciones positivas significativas con 11 de las 12 variables estudiadas. Respecto al número de hámulus, en un análisis comparativo entre abejas africanizadas y europeas, se reportó que entre las abejas obreras africanizadas y europeas, estadísticamente no existen diferencias (26) ; los resultados de este trabajo también confirman esa condición al no encontrar el número de hámulus como una característica discriminante entre ambas razas. En relación a que el patrón morfométrico de las abejas africanas es más pequeño, y que las europeas son más grandes (3,27,28), bajo las condiciones de este trabajo se encontró que si bien, la características morfométricas son diferentes estadísticamente, la diferencia en promedio es muy estrecha, lo cual concuerda con diversos investigadores que afirman que las abejas africanizadas son muy difíciles de diferenciar morfométricamente, y que en la actualidad se tienen abejas africanizadas con características más europeas o viceversa (29,30) .…”
Section: Discussionunclassified
“…Developmental homeostasis results from the joint action of genes, producing a developmental pattern (Del Lama et al, 2002). Because of the rapid and intense environmental change caused by anthropogenic activities, such as deforestation and pollution, there is growing concern about the ecological and evolutionary consequences of human activities on natural populations (Polak et al, 2002).…”
Section: Introductionmentioning
confidence: 99%